IMPLEMENTASI NILAI-NILAI PANCASILA DALAM KEHIDUPAN BERMASYRAKAT DI ERA DIGITAL - Akdila Bulanov; Bella Asifa Purba; Sarifatul Aini; Flora Intan Cahyani; Indra Saputra Junefri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The rapid development of digital technology has significantly transformed social interactions, communication patterns, and information dissemination within society. While digitalization provides various benefits such as easier access to information and broader communication networks, it also creates challenges including the spread of misinformation, cyberbullying, hate speech, and declining social ethics. Therefore, the values of Pancasila as the ideological foundation of Indonesia remain highly relevant in guiding citizens' behavior in the digital era. This study aims to analyze the implementation of Pancasila values in social life amidst digital transformation. The research employs a qualitative descriptive method through a literature review of books, journals, and scientific articles. The findings indicate that the implementation of Pancasila values can be realized through ethical digital behavior, respect for diversity, responsible participation in digital communities, and the promotion of social justice through technology. Pancasila serves as a moral framework for creating a responsible, inclusive, and civilized digital society.